Evaluasi Pembelajaran Pemrograman Paralel dengan Materi Berbasis Animasi - Dwi Chandra (Jurnal Ilmiah ESAI, 2016)
Parallel programming is a method to solve problem with application which run together. It can save time and hardware resources. Parallel programming subject is interesting because it needs basic knowledge about programming and networking. Teaching materials which contain animation help the students to understand the subject. It really helps to explain about the parallel process. The aims of this research are to know the impact of teaching method using animation and the part of the course that must be explained carefully. After the five month research, it is found that the animation in parallel programming subject can give positive impact on the students.Â Keywords parallel, programming, teaching, process, material.